O processo estratégico em médios negócios paulistanos: o percurso do plano à prática - Blandy, Beatriz de Azevedo (2011)
Exploratory and qualitative study of strategic process, by approach that considers strategy as a practice. This approach receives contributions of philosophy (pragmatism) and social sciences, appropriating the concept of social practice and applying it to studies of management. It also benefits from contributions coming from the Carnegie Tradition, Neo-Institutional Theories, Situational Learning and Actor- Network theory. Through discourse analysis of nine interviews with strategists and executives from midsize businesses, it presents a typology of stages that combines and clarifies aspects of the strategizing from the practitioner s point of view. In this sense, uses excerpts from the speech of interviewees, taking advantage of the main themes addressed by them as evidence of the constituent aspects of each stage